La traversée aérienne de l'Atlantique - F. H.
An account of several different 1919 attempts to achieve transatlantic flight, including the failed attempt of Hawker and Mackenzie-Grieve who left from Newfoundland. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.